231k views
2 votes
3z > -36

help?? Quikly pls!!

2 Answers

0 votes

Answer,

z > -12

Explanation,

Divide both sides by 3,

3z/3 = -36/3

= z > -12

On a number line it would look like this,


3z > -36 help?? Quikly pls!!-example-1
User Hannojg
by
5.4k points
2 votes

Hi there!

Answer:

z>-12

Explanation:

distributive property: ⇒ a(b+c)=ab+ac

divide by 3 both sides of an equation.

3z/3>-36/3

simplify.

-36/3=-12

36/3=12

36/12=3

12*3=36

3*12=36

z>-12

Hope this helps!

-Charlie

Have a great day!

User ErikH
by
5.5k points